2019
DOI: 10.1111/jcpe.13101
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic agents exacerbate periodontal inflammation and aggravate experimental periodontitis

Abstract: Aim This study evaluated the effects of 5‐fluorouracil (5‐FU) and cisplatin (CIS) in healthy periodontal tissues and in the early stages of experimental periodontitis (EP) in rats. Methods One hundred and eighty male rats were divided into three groups, which were submitted to the following systemic treatments: physiological saline solution (PSS); CIS and 5FU. Each group was subdivided into two subgroups: without (NEP) and with (EP) induction of EP. Animals were euthanized at 3, 5 and 7 days post‐treatment. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 37 publications
(46 reference statements)
3
13
0
7
Order By: Relevance
“…Importantly, our study showed higher immunolabelling pattern of TNF-α and IL-1β in NEP-5FU and NEP-CIS when compared with NEP-PSS. This result represents increased expression of proin ammatory cytokines in healthy periodontal tissues and corroborates with Gusman et al 2019 [15], that while assessing the in uence of 5-FU and CIS on healthy periodontium at 3, 5 and 7 days, also observed higher immunolabelling pattern of TNF-α and IL-1β.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Importantly, our study showed higher immunolabelling pattern of TNF-α and IL-1β in NEP-5FU and NEP-CIS when compared with NEP-PSS. This result represents increased expression of proin ammatory cytokines in healthy periodontal tissues and corroborates with Gusman et al 2019 [15], that while assessing the in uence of 5-FU and CIS on healthy periodontium at 3, 5 and 7 days, also observed higher immunolabelling pattern of TNF-α and IL-1β.…”
Section: Discussionsupporting
confidence: 90%
“…NEP-5FU and EP-5FU were treated with 5-FU, and NEP-CIS and EP-CIS were treated with CIS. Each animal received two intraperitoneal injections of either PSS (Equiplex Indústria Farmacêutica, Aparecida de Goiânia, GO, Brazil), 5-FU (Fluorouracila, 250 mg/10 mL, Eurofarma Laboratórios, São Paulo, SP, Brazil) or CIS (Fauldcispla, 10 mg/10 ml, Libbs Farmacêutica, São Paulo, SP, Brazil) at day 0 (5-FU, 60 mg/Kg; CIS, 5 mg/Kg) and day 2 (48 h later) (5-FU, 40 mg/Kg; CIS, 2,5 mg/Kg), in accordance with Gusman et al (2018) [15]. At day 0, after general anesthesia (cloridrato de cetamina − 70 mg/Kg [Syntec, Santana de Parnaíba, SP, Brazil], cloridrato de xilazina − 6 mg/Kg [Syntec, Santana de Parnaíba, SP, Brazil], intramuscular injection), a #24 (Corrente Algodão n°24, Coats Corrente, São Paulo, SP, Brazil) cotton thread was placed around both lower rst molars to induce EP in groups EP-PSS, EP-5FU and EP-CIS [17,18].…”
Section: Experimental Groupssupporting
confidence: 84%
See 1 more Smart Citation
“…NEP-5FU and EP-5FU were treated with 5-FU, and NEP-CIS and EP-CIS were treated with CIS. Each animal received two intraperitoneal injections of either PSS (Equiplex Indústria Farmacêutica, Aparecida de Goiânia, GO, Brazil), 5-FU (Fluorouracila, 250 mg/10 mL, Eurofarma Laboratórios, São Paulo, SP, Brazil) or CIS (Fauldcispla, 10 mg/10 ml, Libbs Farmacêutica, São Paulo, SP, Brazil) at day 0 (5-FU, 60 mg/Kg; CIS, 5 mg/Kg) and day 2 (48 h later) (5-FU, 40 mg/Kg; CIS, 2,5 mg/Kg), in accordance with Gusman et al (2018) [15].…”
Section: Experimental Groupssupporting
confidence: 84%
“…Срок пользования подобной шины определяется имеющейся подвижностью зубов, гигиеной полости рта и методами терапевтического лечения заболеваний тканей пародонта. Недостатками этого метода являются отсутствие эстетики, возможность травмирования здоровых зубов, вероятность возникновения маргинального пародонта, отсутствие точности [65].…”
Section: Clinical Medicineunclassified